Variasi Konsentrasi Air Limbah Cucian Laundry dalam Menentukan Range Finding Test - Hanarisanty, Lina; Roselyn Indah Kurniati; Arini Wulan Sari; Ferdy Ashari Syawal (Jurnal Serambi Engineering, 2026)
Laundry wastewater contains phosphates, detergents and bleaching agents which are harmful to the environment if not treated first. Phytoremediation is an environmentally friendly technology that uses plants to treat wastewater, including laundry wastewater. One such plant is Eichhornia crassipes, also known as water hyacinth. Prior to phytoremediation, acclimatisation and Range Finding Tests (RFTs) were conducted to determine the tolerance limits of the water hyacinth to laundry wastewater concentrations. Acclimatisation took place over 7 days, during which time RFT tests were conducted with wastewater concentration variations of 0%, 30%, 50%, 70% and 100%. Additionally, wet and dry weight measurements were carried out after the RFT tests. During acclimatisation, the water hyacinth plants thrived in the fresh conditions, producing new shoots and fibrous roots. The RFT tests showed that the optimal wastewater concentration was 30 mg/L, as evidenced by green leaves and healthy roots. The greatest decreases in wet weight of the roots and leaves (amounting to 29.99 g and 38.95 g respectively) occurred at a concentration of 0 mg/L. The greatest decrease in wet weight of the stems (76 g) occurred at a concentration of 50 mg/L. Wet and dry weight measurements were conducted to determine the absorbed water content. Therefore, water hyacinth plants can serve as phytoremediators in further liquid waste treatment processes.